Curriculum Design Innovations for Multilingual Education in English Classes at STAI Nurul Ilmi Tanjungbalai - Fuziernisa Fahmi (Universitas Al-Qolam Malang, 2026)
This study aims to explore innovative approaches in curriculum design to support multilingual education within English classes at STAI Nurul Ilmi Tanjungbalai. The research focuses on identifying effective curriculum strategies that accommodate the linguistic diversity of students and enhance their English language proficiency while respecting their native languages. A qualitative research methodology was employed, involving curriculum analysis, classroom observations, and interviews with educators and students. Data were collected over a semester and analyzed using thematic content analysis to uncover the key elements of successful curriculum innovations in a multilingual educational context. The findings reveal that integrating culturally responsive materials, flexible lesson plans, and collaborative learning activities significantly improves student engagement and language acquisition. Additionally, the curriculum innovations help students navigate between multiple languages effectively, fostering better communication skills and academic performance. This study contributes valuable insights for educators and curriculum developers aiming to enhance multilingual education in similar academic settings.